Receptive knowledge of nouns and collocations and the impact on English skill performances - Hoang, Minh Tran; Waluyo, Budi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Interests in examining the roles of receptive vocabulary knowledge and collocational knowledge and competence on EFL learners’ proficiency have grown considerably; yet, the extent of how EFL learners’ receptive knowledge of noun, verb-noun collocations, and nounpreposition collocations impact their English skill performances is still insufficiently researched. To address such gaps, this study specifically explored Thai EFL learners’ receptive knowledge of nouns and collocations and its impact on English skill performances. Three types of receptive vocabulary tests were created by using high-frequency nouns taken from the Academic Vocabulary List (AVL), which became the basis of selecting verb-noun lexical collocations and noun-preposition grammatical collocations. The tests were validated by a pilot study, then distributed to the 2nd year students (N = 135; 28 males; 107 females) at Walailak University, Thailand. The results of the tests were analyzed by using descriptive statistics, independent t-test, ANOVA, and multiple linear regressions. It was revealed that Thai EFL learners, who participated in this study, had insufficient knowledge of noun, either in form or in meaning, and encountered complexities in identifying lexical and grammatical collocations. Receptive knowledge significantly predicted learners’ performance in reading tasks. The findings of this study indicate the urgent need to include collocations into English teaching as Thai EFL learners seem unable to acquire them on their own; besides, the insufficient knowledge of the form and meaning of nouns may imply a deeper problem in Thai EFL learners’ proficiency in grammatical structure. Therefore, it is important to emphasize that English teaching and learning materials, e.g., textbooks and modules, as well as course design and instruction at the university level in Thailand need to include explicitly integrated lessons of nouns (form and meaning) and collocations to facilitate the development of knowledge in such areas.